Migration and transformation of alkali/alkaline earth metal species during biomass and coal co-gasification: A review - Wei, Juntao; Wang, Miao; Xu, Deliang; Shi, Lei; Li, Bin; Bai, Yonghui; Yu, Guangsuo; Bao, Weina; Xu, Jie; Zhang, Hong; Zhang, Shu (Fuel processing technology, 2022)
Co-gasification of biomass and coal is a promising technology for clean and high-efficiency utilization of these two carbon resources. Alkali/alkaline earth metal species (AAEMs) in gasification feedstock not only are the key factors for the synergy behavior on co-gasification reactivity, but also show great relationships with the slagging, fouling and corrosion issues in practical application. Therefore, it is necessary to make a clear understanding of the migration and transformation law of AAEMs in the co-gasification process. This paper made a detailed summary of the main detection methods for AAEMs migration and transformation during co-gasification. The influencing factors of AAEMs migration and transformation in co-gasification process were systematically reviewed. Migration and transformation pathways of AAEMs during co-gasification were also proposed. Additionally, relationship between AAEMs migration and transformation and the synergy of co-gasification was deeply discussed. Finally, the research prospects were put forward based on this review.